The Prospective Synergy of Antitubercular Drugs With NAD Biosynthesis Inhibitors - Rohde, Kyle H.; Sorci, Leonardo (Frontiers in Microbiology, 2021)
Given the upsurge of drug-resistant tuberculosis worldwide, there is much focus on developing novel drug combinations, allowing shorter treatment duration and a lower toxicity profile. NAD biosynthesis targeting is acknowledged as a promising strategy to combat drug-susceptible, drug-resistant, and latent tuberculosis (TB) infections. In this review, we describe the potential synergy of NAD biosynthesis inhibitors with several TB-drugs in prospective novel combination therapy. Despite not directly targeting the essential NAD cofactor's biosynthesis, several TB prodrugs either require a NAD biosynthesis enzyme to be activated or form a toxic chemical adduct with NAD(H) itself. For example, pyrazinamide requires the action of nicotinamidase (PncA), often referred to as pyrazinamidase, to be converted into its active form. PncA is an essential player in NAD salvage and recycling. Since most pyrazinamide-resistant strains are PncA-defective, a combination with downstream NAD-blocking molecules may enhance pyrazinamide activity and possibly overcome the resistance mechanism. Isoniazid, ethionamide, and delamanid form NAD adducts in their active form, partly perturbing the redox cofactor metabolism. Indeed, NAD depletion has been observed in Mycobacterium tuberculosis (Mtb) during isoniazid treatment, and activation of the intracellular NAD phosphorylase MbcT toxin potentiates its effect. Due to the NAD cofactor's crucial role in cellular energy production, additional synergistic correlations of NAD biosynthesis blockade can be envisioned with bedaquiline and other drugs targeting energy-metabolism in mycobacteria. In conclusion, future strategies targeting NAD metabolism in Mtb should consider its potential synergy with current and other forthcoming TB-drugs.